Experience of localized flooding predicts urban flood risk perception and perceived safety of nature-based solutions - Li, Jiayang; Nassauer, Joan Iverson; Webster, Noah J.; Preston, Stephanie D.; Mason, Lisa Reyes (Frontiers in Water, 2022)
Understanding community members’ flood risk perceptions is critical for developing new approaches to managing flood risks for climate resilience. “Risk as feelings” has informed research on how people perceive flood risks based on intuition and personal experiences, complementing experts’ technical assessment. However, attention has been primarily on riverine and coastal flooding. We expand the “risk as feelings" concept to investigate community members’ risk perceptions of urban pluvial flooding as well as perceived safety of novel vs. familiar nature-based solutions (NBS). For the novel practice, we focus on floodable sites that temporarily inundate urban open spaces under storm conditions. For the familiar practice, we focus on retention ponds that store runoff under storm conditions. Data were collected through visualization-assisted surveys of residents from high and low flood hazard areas in three US cities (N = 884). We found that over half of respondents indicated some degree of worry about stormwater-related damage, and overall, respondents perceived floodable as less safe than retention ponds under storm conditions. Further, respondents who had more frequently experienced localized flooding near their homes were more worried about potential property damage caused by flooding. They also perceived floodable sites as less safe under storm conditions. However, more frequent experience of localized flooding was not associated with perceived safety of retention ponds under storm conditions. Some other contextual and socio-demographic factors (e.g., prior stormwater-related property damage, knowledge of and involvement in stormwater management issues, gender, age, race, and having children) also had notable effects on flood risk perception and perceived safety of NBS. We discuss the implications of these findings for urban flood risk management and NBS development.